„Dzisiaj kwiatem, jutro słomą” – tajemnica ludzkiego przemijania w Ps 90 - Tułodziecki, Tomasz (Verbum vitae, 2013)
Psalm 90 stands at a critical juncture in the overall scheme of the Psalter. It is the first psalm in the small collection of Ps 90–106 which constitutes Book IV of the Psalter. This song, which begins as a mourning cry, then rises to an angry complaint, and seems to conclude in a desperate resignation, at the end arrives at a breadth and depth of meditation on the coherence of divine actions and the corresponding human reaction. The Hebrew verb turn/return occurs three times in Psalm 90. It is the verb used in the prophetic literature to call on the people to return to their God. In Ps 90:3 God is pictured as (re)turning humans to the dust whence they came by ordering, “Return, children of mankind!”. Surprisingly, however, in the v.13, which constitutes the turning-point of the entire psalm, the psalmist calls on YHWH to “repent” and to show a change of heart. God is asked to be mindful of the fact that humans flourish for but a morning and they fade by evening (vv. 5-6). The author beseeches that the covenant loyalty (Hesed ) of YHWH might satisfy his servants in the morning, so that rejoicing and gladness may follow for a new lifetime. In this context, the references to God’s “work” and to his “glorious power” (v. 16) seem to take on a double meaning. The appeal is not only for a restoration of the nation of Israel by powerful acts of divine intervention. The appeal is, perhaps even more, for YHWH to show his work, the work of compassion (v. 13), and to make his power known by his covenant loyalty (v. 14) and favor (v. 17).